Multidisciplinary approach in the diagnosis of acute leptospirosis in dogs naturally infected by Leptospira interrogans serogroup Icterohaemorrhagiae: A prospective study. (August 2021) - Paz, Lucas Nogueira; Dias, Carla Silva; Almeida, Daniela Santos; Balassiano, Ilana Teruszkin; Medeiros, Marco Alberto; Costa, Federico; Silva, Danielle Nascimento; Reis, Joice Neves; Estrela-Lima, Alessandra; Hamond, Camila; Pinna, Melissa Hanzen
Highlights: Multidisciplinary approach enabled the identification of acute leptospirosis in dogs. Identification of autochthonous strains are critically important to epidemiological studies and the reformulation of prophylactic methods. Canine leptospirosis is frequently associated with Leptospira interrogans sg. Icterohaemorrhagiae sv. Icterohaemorrhagiae/Copenhageni. 26.3 % (10/38) of the animals in the confirmed group were vaccinated against leptospirosis. Abstract: Leptospirosis, a zoonotic disease with worldwide distribution, is caused by spirochetes of the genus Leptospira . In dogs, this disease is frequently misdiagnosed. Few studies have attempted to associate the detection of Leptospira spp. infection with clinicopathological and renal histopathological findings using a multidisciplinary approach. The present study isolated and characterized Leptospira spp. obtained from naturally infected dogs and described relevant clinical and histopathological findings. Blood and urine were collected from 57 dogs with clinical symptomatology suggestive of leptospirosis; 38 cases were confirmed by PCR in urine or by culture or microscopic agglutination testing (titers ≥800). A total of 12 strains of pathogenic Leptospira were isolated from the studied dogs (seven in blood, four in urine and one in both blood and urine samples). All isolates were characterized as Leptospira interrogans serogroup Icterohaemorrhagiae. Of the confirmed cases, almost one-third of the animals had been vaccinated. Our analysis of laboratory testing revealed that azotemia and proteinuria were statistically significant predictors of infection. The main histopathological findings seen in kidney tissues were necrosis, degeneration, tubular regeneration, mononuclear inflammatory infiltrate and congestion. A multidisciplinary approach involving clinicopathological and histopathological characterization of renal involvement can aid in the identification of acute leptospirosis infection.